Metabolome Analysis Revealed the Mechanism of Exogenous Glutathione to Alleviate Cadmium Stress in Maize (Zea mays L.) Seedlings - Wang, Runfeng (Plants (Basel), 2021)
Cadmium (Cd) is one of the major heavy metal pollutants in the environment and imposes severe limitations on crop growth and production. Glutathione (GSH) plays an important role in plant Cd tolerance which is able to scavenge stresses-induced reactive oxygen species (ROS) and is involved in the biosynthesis of phytochelatins (PCs). Our previous study revealed that Cd stress affects maize growth, and the GSH treatment could relieve Cd stress in maize seedlings. In this study, we attempted to characterize the metabolomics changes in maize leaves and roots under Cd stress and exogenous GSH conditions. We identified 145 and 133 metabolites in the leaves and roots, respectively. Cd stress decreased the tricarboxylic acid cycle (TCA cycle) metabolism and increased the amino acid contents in the leaves, while it decreased the amino acid contents, increased the TCA cycle metabolism, the sugar contents, and shikimic acid metabolism in the roots. On the other hand, exogenous GSH increased the GSH content, changed the production of metabolites related to antioxidant systems (such as ascorbic acid-related metabolites and flavonoid-related metabolites), and alleviated lipid peroxidation, thereby alleviating the toxic effect of Cd stress on maize. These findings support the idea that GSH alleviates Cd-induced stress in maize and may help to elucidate the mechanism governing Cd-induced stress and the GSH-driven alleviation effect.